Online Education Systems in Scandinavian and Australian Universities: A Comparative Study - Morten Paulsen (Athabasca University Press, 2002)
This article presents a comparative study of online education systems in Norwegian, Swedish, and Australian universities. The online education systems discussed comprise content creation tools and systems for learning management, student management, and accounting. The author of this article arrives at the conclusion that there seems to be a general lack of integration between theses systems in all three countries. Further, there seems to be little focus on standards specifications such as IMS Global Learning Consortium (IMS) and Sharable Content Object Reference Model (SCORM) in higher education in all three countries. It was found that both Norway and Sweden value the importance of nationally developed learning management systems and student management systems; however, this does not seem to be the case in Australia. There also seems to be much more national coordination and governmental coercion concerning the choice of student management systems used in Sweden and Norway, than is the case in Australia. Finally, with regard to online education, the most striking difference between these three countries is that of economic policy. In Australia, education is considered an important export industry. In Norway and Sweden, however, the export of education does not seem to be an issue for public discussion.